The Effects of Applying Biological Control Measures in Greenhouse Cultivation on the Production Efficiency in Ka? District of Antalya Province, Turkey - Türkten, Hatice (European Journal of Sustainable Development, 2017)
Nowadays, in vegetable production, biological pest control practices are recommended to prevent human health and environmental damage even though there has been lacking of economic information. Therefore, the study examined the economic dimension of biological and chemical control measure and aimed to reveal the link between production efficiency and biological pest control practice. Research data were collected from randomly selected 51 farms implemented chemical pest control practice, and 52 farms implemented biological pest control practice by using questionnaire. Cluster analysis was performed to select similar farms from two different groups. Data envelopment analysis (DEA) was used to calculate the efficiency measures such as technical efficiency, allocative efficiency and economic efficiency. Research results showed that farms implemented in biological pest control in pepper production had better technical efficiency and economic efficiency scores comparing to tomato ones, while the reverse was the case for allocative scores. Farms focused only pepper production, implemented biological pest control had better technical efficiency scores compared to chemical ones. Research results also showed that biological pest control in tomato was excessive net profit, biological control costs and pesticide use in greenhouse, while the reverse was the case for pepper. Farmers would increase their technical efficiency if they improve their skills via participating the extension and training programs. Keywords: greenhouse cultivation, biological pest control, production efficiency, Antalya, DEA